2011
DOI: 10.1016/j.jhep.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced toxicity on mitochondria and lipid metabolism: Mechanistic diversity and deleterious consequences for the liver

Abstract: Numerous investigations have shown that mitochondrial dysfunction is a major mechanism of drug-induced liver injury, which involves the parent drug or a reactive metabolite generated through cytochromes P450. Depending of their nature and their severity, the mitochondrial alterations are able to induce mild to fulminant hepatic cytolysis and steatosis (lipid accumulation), which can have different clinical and pathological features. Microvesicular steatosis, a potentially severe liver lesion usually associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
425
2
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 466 publications
(448 citation statements)
references
References 331 publications
(514 reference statements)
9
425
2
12
Order By: Relevance
“…2008; Begriche et al. 2011). Recently, amiodarone was shown to induce ER stress in thyrocytes and lung epithelial cells (Mahavadi et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2008; Begriche et al. 2011). Recently, amiodarone was shown to induce ER stress in thyrocytes and lung epithelial cells (Mahavadi et al.…”
Section: Introductionmentioning
confidence: 99%
“…The most common adverse effects of these compounds include GI manifestations, drowsiness, extrapyramidal symptoms, cardiac effects, elevation of liver enzymes, and obesity, which can be associated with insulin resistance and fatty liver (Melkersson and Dahl 2003; Begriche et al. 2011; De Fazio et al. 2015; Rojo et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and some genetic factors have been speculated widely as the key mechanisms for hepatotoxicity [7]. Microvesicular hepatosteatosis is a typical feature of VPA toxicity and is suggestive of mitochondrial involvement especially involving the β-oxidation [8]. The recent study by Komulainen et al showed the effects of VPA on mitochondria using the HepG2 cell in vitro model and further suggested an essential role of mitochondria; VPA inhibited mitochondrial respiration resulting in mitochondrial dysfunction, oxidative stress, and increased cell death [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence of the mitotoxicity of certain antidiabetic (e.g., metformin) (11), anticancer (e.g., doxorubicin) (13), antiparasitic (e.g., atovaquone) (14), antiviral (e.g., zidovudine) (15), antiepileptic (valproic acid [VPA]) (10), anesthetic (e.g., propofol) (16), anti-inflammatory (e.g., indomethacin) (17), and antiarrhythmic (e.g., carvedinol) (11) drugs. Therefore, taking such drugs can lead to organ damage, particularly damage to the liver (18), kidneys, heart (19), or skeletal muscles (20). Interestingly, these issues affect the most aerobically poised organs (heart and kidneys) or organs exposed to higher concentrations of the drug (liver).…”
Section: Mitochondrial Drugs Toxicitymentioning
confidence: 99%